Juridical Relations between Freedom of Artistic Expression and Protection of the Dignity of Religion in the Light of a Lawsuit over Theatrical Performances in the Czech Republic - Němec, Damián (Philosophy and Canon Law, 2023)
This paper deals with the legal regulation of the relationship between two human rights, freedom of artistic creation and protection of the value of religion as part of freedom of religion in the Czech Republic. It first gives an overview of three models of this relationship in three historical epochs: the period of democratic Czechoslovakia in the years 1918 to 1948 (excluding the period of World War II, where the protection of human rights was completely ignored), the period of domination of the Communist Party of Czechoslovakia in 1948 to 1989, that is, a period of general violations of human rights, and in a democratic society from 1989 (until 1992 in Czechoslovakia, from the disintegration of the Czechoslovak federation to January 1, 1993, in the Czech Republic). Most attention is paid to litigation caused by the presentation of two theater performances at the Brno Theater Festival in 2018. Both performances were directed by the Croat Oliver Frljić, known for controversial means of expression, often with a religious theme. The ensuing lawsuit, in which the then president of the Czech Bishops’ Conference was one of the plaintiffs, showed that the general courts preferred the protection of artistic freedom in the conflict between the two constitutionally guaranteed freedoms with only one significant restriction: vituperation or downsizing of beliefs. However, the dispute is not yet fully resolved: the plaintiffs have filed a complaint with the Constitutional Court of the Czech Republic, which has not yet ruled on the matter. Consequently, an application to the European Court of Human Rights in Strasbourg cannot be ruled out.